Dynamics of DNA Methylation during Early Development of the Preimplantation Bovine Embryo - Dobbs, Kyle B. (2013)
There is species divergence in control of DNA methylation during preimplantation development. The exact pattern of methylation in the bovine embryo has not been established nor has its regulation by gender or maternal signals that regulate development such as colony stimulating factor 2 (CSF2). Using immunofluorescent labeling with anti-5-methylcytosine and embryos produced with X-chromosome sorted sperm, it was demonstrated that methylation decreased from the 2-cell stage to the 6-8 cell stage and then increased thereafter up to the blastocyst stage. In a second experiment, embryos of specific genders were produced by fertilization with X- or Y-sorted sperm. The developmental pattern was similar to the first experiment, but there was stage × gender interaction. Methylation was greater for females at the 8-cell stage but greater for males at the blastocyst stage. Treatment with CSF2 had no effect on labeling for DNA methylation in blastocysts. Methylation was lower for inner cell mass cells (i.e., cells that did not label with anti-CDX2) than for trophectoderm (CDX2-positive). The possible role for DNMT3B in developmental changes in methylation was evaluated by determining gene expression and degree of methylation. Steady-state mRNA for DNMT3B decreased from the 2-cell stage to a nadir for D 5 embryos >16 cells and then increased at the blastocyst stage. High resolution melting analysis was used to assess methylation of a CpG rich region in an intronic region of DNMT3B. Methylation percent decreased between the 6-8 cell and the blastocyst stage but there was no difference in methylation between ICM and TE. Results indicate that DNA methylation undergoes dynamic changes during the preimplantation period in a manner that is dependent upon gender and cell lineage. Developmental changes in expression of DNMT3B are indicative of a possible role in changes in methylation. Moreover, DNMT3B itself appears to be under epigenetic control by methylation. © 2013 Dobbs et al.